Cortical responses to whole‐body balance perturbations index perturbation magnitude and predict reactive stepping behavior. (20th September 2020) - Solis‐Escalante, Teodoro; Stokkermans, Mitchel; Cohen, Michael X.; Weerdesteyn, Vivian
Abstract: The goal of this study was to determine whether the cortical responses elicited by whole‐body balance perturbations were similar to established cortical markers of action monitoring. Postural changes imposed by balance perturbations elicit a robust negative potential (N1) and a brisk increase of theta activity in the electroencephalogram recorded over midfrontal scalp areas. Because action monitoring is a cognitive function proposed to detect errors and initiate corrective adjustments, we hypothesized that the possible cortical markers of action monitoring during balance control (N1 potential and theta rhythm) scale with perturbation intensity and the eventual execution of reactive stepping responses (as opposed to feet‐in‐place responses). We recorded high‐density electroencephalogram from eleven young individuals, who participated in an experimental balance assessment. The participants were asked to recover balance following anteroposterior translations of the support surface at various intensities, while attempting to maintain both feet in place. We estimated source‐resolved cortical activity using independent component analysis. Combining time‐frequency decomposition and group‐level general linear modeling of single‐trial responses, we found a significant relation of the interaction between perturbation intensity and stepping responses with multiple cortical features from the midfrontal cortex, including the N1 potential, and theta, alpha, and beta rhythms. Our findings suggest that the cortical responses to balance perturbations index the magnitude of a deviation from a stable postural state to predict the need for reactive stepping responses. We propose that the cortical control of balance may involve cognitive control mechanisms (i.e., action monitoring) that facilitate postural adjustments to maintain postural stability. Abstract : This study shows a significant relation between the perturbation‐related N1 potential and the interaction between perturbation intensity with ensuing corrective postural response; which indicates that, for a given perturbation intensity, the magnitude of the N1 potential (and accompanying cortical oscillations) may predict the execution of stepping and feet‐in‐place responses. This provides further evidence that cognitive control mechanisms may regulate reactive postural adjustments.